2010
DOI: 10.1177/1077800410389442
|View full text |Cite
|
Sign up to set email alerts
|

Making Sense of an Untold Story: A Personal Deconstruction of the Myth of Motherhood

Abstract: This article critically explores the modern myth of motherhood through my personal life story as a mother. Feelings of rejection of the demands and expectations of my motherly role led me to research social histories and feminist analyses for common maternal images. My explorations made me believe that the myth of motherhood is a relatively new social construction aiming, among others, to oppress and exploit women. Surveying the institution of motherhood as a mechanism of control, I openly discuss what I perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 16 publications
0
11
0
6
Order By: Relevance
“…Moreover, the state of Israel provides generous funding for infertility treatment technologies and has been known to have the highest number of fertility clinics per capita in the world (Kahn, 2000;Portuguese, 1998: 154). 1 According to the Israeli feminist scholar Daphna Hacker, being a mother is viewed as a condition for a full life (Hacker, 2001); as a result, single and childless women are the subjects of a constant social scrutiny (Donath, 2011;Hager, 2011;Lahad, 2012). Evidently, Israel is not the only place in which single women are scrutinized and criticized, and one can find similar findings about single women worldwide.…”
Section: Theoretical Background and Settingmentioning
confidence: 81%
“…Moreover, the state of Israel provides generous funding for infertility treatment technologies and has been known to have the highest number of fertility clinics per capita in the world (Kahn, 2000;Portuguese, 1998: 154). 1 According to the Israeli feminist scholar Daphna Hacker, being a mother is viewed as a condition for a full life (Hacker, 2001); as a result, single and childless women are the subjects of a constant social scrutiny (Donath, 2011;Hager, 2011;Lahad, 2012). Evidently, Israel is not the only place in which single women are scrutinized and criticized, and one can find similar findings about single women worldwide.…”
Section: Theoretical Background and Settingmentioning
confidence: 81%
“…For example, there has been discussion about the "Myth of Motherhood," based on which unrealistically high expectations are placed on mothers by society, which shapes their experience as parents (fathers, in turn, are considered to be good parents simply by spending time with their children) (e.g., Douglas and Michaels 2004;Hagger 2011). Consequently, mothers may experience considerable guilt for not being perfect, as expected by themselves or by society (Hagger 2011). Douglas and Michaels (2004) suggested that "motherhood has become a psychological police state" (p. 6), meaning that in addition to societal judgment, mothers evaluate each other and themselves as mothers.…”
Section: Discussionmentioning
confidence: 99%
“…One personality characteristic which may be particularly crucial in the development of burnout is multidimensional perfectionism (for a review, see Hill and Curran 2016) consisting of self-oriented perfectionism (i.e., high self-standards accompanied by harsh self-criticism) and socially prescribed perfectionism (i.e., perceived high standards from others; Hewitt and Flett 1991). Although parents have been shown to be both harsh on themselves and experience pressure in their parenting from other people (Douglas and Michaels 2004;Hagger 2011), the relationship between parental burnout and multidimensional perfectionism has so far not been investigated. Furthermore, studies including both family background and children's characteristics, as well as parental personality factors as predictors of parental burnout are rare (Kawamoto et al 2018;Mikolajczak et al 2018b).…”
mentioning
confidence: 99%
“…Am I a 'docile body' (Foucault 1979), I wonder, victim of constraining discourses that shape and produce my body in accordance with dominant social norms? Hager (2011) and Murphy (1999) suggest that 'good' mothers are constructed as those who sacrifice their time and comfort, and endure suffering for the benefit of their children. Could I be actively trying to position myself as a 'good' mother?…”
Section: Autoethnographymentioning
confidence: 98%